External Morphological Study of the species Diplacodes nebulosa (Fabricius) (Odonata :Libellulidae); New Record for Iraq - Intessar F. Abd (Journal of Madenat Alelem University College, 2013)
External morphological of the species Diplacodes nebulosa (Fabricius) belong to family : Libellulidae, suborder Anisoptera, order Odonata was studied using preserved specimens from College of Agriculture Museum, Baghdad University, collected from Derbendekhan region during 1986. The study included: detailed description of most body parts (head, thorax, abdomen and their appendages), identification and recognition of species, in addition to study male genitalia. The species Diplacodes nebulosa (Fabricius) was regarded as new record for Iraqi fauna of Odonata.